Agency: The Revolutionary Act: A Dialectic of Sex/Gender in The Female Man. - CORTIEL, JEANNE (Demand My Writing: Joanna Russ, Feminism, Science Fiction, 1999)
Chapter 3 of the book "Demand My Writing: Joanna Russ/Feminism/Science Fiction," by Jeanne Cortiel is presented. According to this chapter, Russ' book "The Female Man" partially reflect the radical materialist feminist premise that places women as a sex-class under the dual system of oppression formed by capitalism and patriarchy. It states that the sex-class antagonism which is grounded in women's reproductive function also constructs the dynamics of interactions between males and females in the writings of Russ.